Perceived entrepreneurial success characteristics: A study among ex-servicemen entrepreneur in Malaysia - Mahmood, Rosli (Universiti Utara Malaysia, 1995)
The study on a group of successful ex-servicemen entrepreneurs in Malaysia revealed that internal factors such as personality and ability of the individuals contributed to their entrepreneurial success. On the other hand, luck, inheritance and financial support from family were found to be the least important factors in contributing to the success of these entrepreneurs. The finding of this study is particular important to the policy makers in designing the entrepreneurial development programme for retiring and retired servicemen. More emphasis should be given to moulding a person's character and the training of skills relating to creativity and problem solving.